Evaluation of bim implementation requirements affecting iraqi construction firms - Hussein Mahmood, Hamada (2017)
Construction industry is one of a challenging industry. Similarly, to other countries, the construction industry in Iraq is facing the same repeating challenges of cost overrun, delays and low quality. The advancement of technology in construction industry, nevertheless has provide many solutions to minimize the challenges and one of them is Building Information Modelling (BIM). In Iraq, the use of BIM is still relatively low and one of the factor is many of the companies have limited information and knowledge regarding to the BIM implementation requirements. This is therefore has directed to the aim of this research which is to determine and identify the BIM implementation requirements. To achieve the aim of this research, mixed method by combining qualitative and quantitative approach were engaged. It was started by conducting literature reviews to develop BIM theoretical framework. 4 elements (Process, Management, Technology, and people) include 13 categories were identified in the literature review by comparing seven BIM implementation models and there were (legal issues, Policy, Resistance to change, Time and cost, Professional management, Leadership, Knowledge and skills, Software, Hardware, Education and training, Planners who understand BIM, Request from owner, and Acceptance by staff). The theoretical framework was later on be used as a basis to explore in depth BIM implementation requirements in case studies that involved three companies. In the case studies, three contractors and five respondents with civil engineering and architects background were involved. By engaging semi structure interview and content analysis method, 31 BIM implementation requirements were identified. Succeeding after that, a conceptual framework was developed. In validation process, a quantitative approach was engaged by first developing a questionnaire, based on the conceptual framework. The questionnaire was then sent to 230 respondents to determine the importance of each BIM implementation requirement. From that number, only 53 respondents that replied back to the researcher. The analysis of variance ANOVA was later been conducted for data to find out the variance differences among the specialists who participated in the questionnaire by using p-value. The results show that no statistical differences among the participant's answers after identifying the p-value which was > 0.05. Meanwhile, Relative Importance Index method (RII) was used to determine the importance of each BIM implementation requirement, by adopting the SPSS software version 22. The results from the questionnaire showed that all the 31 implementation requirements were important, with factor “Adjustment the Contract According to BIM implementation requirements” and “satisfaction of staff on the implementation the BIM in their projects”, both have scored RII value of 0.875 followed by factor “requirements of construction market to implement and apply the BIM in the projects” has value RII= 0.856, then ”Importance of a new roles and responsibilities in the companies to adopt BIM” and “Adoption the agreed standards in BIM implementation”, both have RII=0.852. The lowest RII value belongs to “selection of appropriate hardware quality for using it by operators” with RII value 0.675. Process element is the most important with average RII= 0.837, while the lowest importance is technology element with RII= 0.777. This study has contributed to knowledge by providing the understanding of BIM implementation requirements specifically in Iraq and fill the knowledge gaps in the adoption of modern technologies in the Iraqi construction industry. These requirements can be used as a guideline to assist the BIM implementation and application in Iraqi construction companies. The study recommended that the Government of Iraq must play active role in the adoption of the BIM, by encouraging the construction companies and open the door for investment to the BIM experienced foreign companies to implement BIM in Iraq.